IMPLEMENTASI MODEL POE (PREDICTION, OBSERVATION, EXPLANATION) PADA PEMBELAJARAN GERAK LURUS DI MAN - Yeni Lusiana; Sutarto Sutarto; Albertus Djoko Lesmono (FKIP Universitas Jember, 2017)
This article was the result of research of the influence POE (Prediction, Observation, Explanation) model to cognitive physics learning achievement and science process skills of students in physics learning at MAN. The purposes of the research were to study the influence of model to cognitive physics learning achievement and science process skills of students. This research was conducted in MAN 2 Jember. This type of research was experimental by post-test only control design. The population in this study were students of class X at MAN 2 Jember of Academic Year 2016/2017. Samples were taken with cluster random sampling, X IPA 2 selected as esperiment class and X IPA 4 selected as control class. The techniques of data collection were test, observation, interviews and documentation. The technique of data analysis used Independent Sample T-Test (SPSS 22). The results were obtained significance value of 0,000 for cognitive physics learning achievement of students and 0,0235 for science process skills of students. It can be concluded that model of POE (Prediction, Observation, Explanation) influence to cognitive learning achievement and science process skills of students. Keywords: POE (Prediction-Observation-Explanation) Learning Model, Cognitive Physics Learning Achievement, Science Process Skills.